Checklist of the fishes collected on the «Santa Maria and Formigas 1990: Scientific Expedition» - Arruda, Luís M. (1992)
The Azores are a group of nine islands stretching eastwards from the Mid-Atlantic ridge, from 36° 55' N and 25° 01' W to 39° 43' N and 31° 07' W. Santa Maria (Sma) is the eastern most island of this archipelago and Formigas (For) is a low jumble of volcanic rock nearby. The ichthyological fauna of these islands is not well known. So, the main purpose of this note is to present a list of the fishes caught on this expedition organized by the Department of Biology of the University or the Azores. Fishes were collected in tidepools mainly with rotenone and (using SCUBA) at depths of about 6, 10, 15 and 25 meters (m) and are deposited in the Museu Bocage, Museu Carlos Machado, J. L. B. Smith Institute, U. S. National Museum or Natural History. The taxonomy or the listed species is given according to Clofnam (HUREAU & MONOD, 1979) and the Clofnam-number is indicated. The records are given in a standard sequence: locality, day, month, depth of water and depth of collection (in meters).